A model to analyze the knowledge management risks in open innovation: proposition and application with the case of GOL Airlines. Issue 3 (23rd August 2021) - Oliva, Fábio Lotti; Paza, Andrei Carlos Torresani; Bution, Jefferson Luiz; Kotabe, Masaaki; Kelle, Peter; Vasconcellos, Eduardo Pinheiro Gondim de; Grisi, Celso Claudio de Hildebrand e; Almeida, Martinho Isnard Ribeiro de; Fischmann, Adalberto Americo
Abstract : Purpose: This study aims to investigate the risks associated with managing the dispersed knowledge in inter-organizational arrangements for innovation. Specifically, it proposes a model to analyze the knowledge management risks in open innovation, applied in four steps. Design/methodology/approach: Initially, the authors carried out a systematic literature review (SLR) on the concepts that connect knowledge management, inter-organizational arrangements for innovation and risks. The SLR results led to a complementary theoretical review on the conceptual elements in question. Based on the findings, the authors have developed a model to analyze the knowledge management risks in open innovation, which was validated by experts. It was then studied the case of GOL Airlines, a company that uses innovation to overcome the paradox between low-cost and full service in the commercial air transportation industry, considering the application and adjustment of the proposed model. Findings: Open innovation is one of the inter-organizational arrangement types most applied in the context of innovation. Relations between agents are the primary sources of risks when managing the dispersed knowledge in these arrangements. The authors have found five main risks associated, namely, risk of the innovative effort does not reach the expected objective, risk of knowledge transfer being ineffective, risk of misappropriation of value, risk of dependency (lock-in) and risk of relations. Practical implications: The practical implication is the proposition of a procedure for applying the model to analyze the knowledge management risks in open innovation, which makes it a prescriptive model for identifying risks. The proposed model is described in four steps, namely, to identify the agents in the environment of the value of open innovation; to identify the types of relations of each agent; to consider the barriers to knowledge management in innovation; and to assess the risks considering the possibilities derived from the agents, their relationships and the barriers. The model is applied in the GOL case and the results are presented. Originality/value: First, it uses a novel approach to investigate open innovation while studying its risks. This approach considers the knowledge is dispersed and flows from one organization to another through a combination of relations inside the environment of value where the open innovation materializes. Second, it contributes to theory development by opening a research front that fuses four areas: risk management, knowledge management, innovation and inter-organizational arrangements. Third, this paper proposes a theoretical model and presents its operationalization. The study aims to make an impact beyond academia and uses a case study to illustrate the model application in a real and interesting open innovation project to support the business model at GOL Airlines.